Chaos and culture : Renzo Piano Building Workshop and the Stavros Niarchos Foundation Cultural Center in Athens - Newhouse, Victoria (2017)
"A history of the design and construction of the Niarchos Foundation Cultural Center in Athens set against the background of the economic and political crisis in Greece"--
Includes bibliographical references.
Keywords: Stavros Niarchos Foundation Cultural Center; Renzo Piano Building Workshop; Architecture and society -- Greece -- History -- 21st century; ARCHITECTURE / Buildings / Public, Commercial & Industrial; ARCHITECTURE / Criticism; ARCHITECTURE / History / Contemporary (1945-).; Athens (Greece) -- Buildings, structures, etc